Inflammatory Marker sTREM-1 Reflects the Clinical Stage and Respiratory Tract Obstruction in Allergic Asthma Bronchiale Patients and Correlates with Number of Neutrophils - Maria Bucova; Magda Suchankova; Martin Dzurilla; Mojmir Vrlik; Helena Novosadova; Eva Tedlova; Stefan Urban; Edita Hornakova; Marianna Seligova; Vladimira Durmanova; Peter Penz; Juraj Javor; et al. (Hindawi Limited, 2012)
The knowledge that asthma is an inflammatory disorder has prompted us to investigate the plasma levels of a new inflammatory marker sTREM-1 that is released from the surfaces of activated neutrophils and monocytes. The plasma levels of sTREM-1 were analysed by a sandwich ELISA test in the cohort of 76 patients with allergic asthma bronchiale and 39 healthy controls. Our results revealed more than 3.5 times higher levels of sTREM-1 in AB patients (92.3 pg/mL ± 125.6) compared with healthy subjects (25.7 pg/mL ± 9.2; P=0.0001). Higher levels of sTREM-1 were found also in patients with exacerbated AB (170.5 pg/mL ± 78.2) compared with nonexacerbated AB patients (59.1 ± 78.2; P<0.0001), patients with respiratory tract obstruction (176.4 pg/mL ± 177.8), than those without obstruction (51.99 pg/mL ± 64.0; P<0.0001) and patients with anti-IgE therapy (P<0.0001). Levels of sTREM-1 correlated with number of leucocytes (P=0.002), and absolute number of neutrophils (P=0.001). Elevated plasma levels of sTREM-1 reflect the severity, state of exacerbation, presence of respiratory tract obstruction in AB patients and together with increased number of neutrophils point to the role of neutrophils in inflammation accompanying AB.